2007
DOI: 10.1016/j.cej.2006.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, mechanical testing and application of high-pressure glass microreactor chips

Abstract: The design, fabrication and high-pressure performance of several in-plane fiber-based interface geometries to microreactor chips for highpressure chemistry are discussed, and an application is presented. The main investigated design parameters are the geometry of the inlet/outlet structure, the manner in which top and bottom wafer are bonded and the way the inlets/outlets turn over into the microfluidic channels.Destructive pressure experiments with H 2 O and liquid CO 2 showed that the maximum pressure that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 30 publications
1
92
0
1
Order By: Relevance
“…[18] In this study, we report oxidative conversion of light alkanes, C 1 -C 3 range, in the presence of cold plasma in a microreactor. [19] The use of a microreactor for plasma processing [20] helps to work at higher pressures instead of the vacuum required in conventional systems. [13] Generation of a DBD at atmospheric pressure in a small and confined reactor space may imply a 1) stronger electric field, 2) more uniform and dense plasma and 3) better control of the residence time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18] In this study, we report oxidative conversion of light alkanes, C 1 -C 3 range, in the presence of cold plasma in a microreactor. [19] The use of a microreactor for plasma processing [20] helps to work at higher pressures instead of the vacuum required in conventional systems. [13] Generation of a DBD at atmospheric pressure in a small and confined reactor space may imply a 1) stronger electric field, 2) more uniform and dense plasma and 3) better control of the residence time.…”
mentioning
confidence: 99%
“…[21] Sandwich thermal bonding of three Pyrex plates (one with and, respectively, the bottom and top plate without a channel) allowed fabrication of the microreactor (Figure 4, right). [19] Gas in-and out-lets were created by powder blasting using alumina particles. Two copper ribbon electrodes were attached, externally, on the top and bottom side of the chip.…”
mentioning
confidence: 99%
“…In addition to etching, through-holes in glass wafers can be made by drilling and powder blasting (Belloy, Sayah, & Gijs, 2000). In general, glass-glass bonding is considered easier than silicon-silicon or polymer-polymer bonding because of the wide variety of methods available for glass (Chiem et al, 2000;Daridon et al, 2001;Jia, Fang, & Fang, 2004;Easley, Humphrey, & Landers, 2007;Tiggelaar et al, 2007). Silicon-glass anodic bonding is also a routine task (Despont et al, 1996;Berthold et al, 2000;Lee et al, 2000).…”
Section: Glassmentioning
confidence: 99%
“…High-p,T micro processing studies from other research groups with new application examples revealed similar effects. Gardenier et al [29] studied the formation of carbamic acid from N-benzylmethylamine and CO 2 using a high-pressure glass microreactor chip. Only by high-pressure operation at 200 bar can the product be formed, whereas at 10 bar no product formation was observed.…”
Section: Process Intensification Through Order-ofmagnitude Reduction mentioning
confidence: 99%